Karakteristik Sastra Arab pada Masa Pra-Islam - Haeruddin Haeruddin (Hasanuddin University, 2016)
It cannot be denied that Arab people own abundant types of culture. One of those types is literature work which was well known by the people from their ancient time. Many common people, however, do not know but faculty members from Arabic Study Program. According to this situation, an effort of more introductions to public regarding the issue is needed. The paper contains important information of the characteristics of Arabic literatures in the era of jahiliyyah (Pre-Islam), such as its background and social life of Arab people in the era. In addition, the paper also contains main issues relating to the themes in the literatures as well as factors influencing Arabic literatures development in the era.